Effects of hydrophobic chain structure on adsorption of fluorocarbon surfactants with either CF3- or H-CF2-terminal groups - Downer, A; Eastoe, J; Pitt, A; Simister, E; Penfold, J (1999)
Tensiometry and neutron reflection (NR) have been used to investigate the adsorption at the air/water interface of four fluorinated surfactants. These compounds were two single-chain carboxylates-sodium perfluorononanoate (NaPFN) and sodium 9H-perfluorononanoate (HNaPFN)- and two double-chain sulfosuccinates-sodium bis(1H,1H-perfluoropentyl)-2-sulfosuccinate (DCF4) and sodium bis(1H,1H,5H-octafluoropentyl)-2-sulfosuccinate (DHCF4). The replacement of a terminal fluorine for hydrogen creates a permanent dipole in the hydrophobic chain tip which significantly affects the surfactant behavior. This change in structure leads to an increase in the critical micelle concentration (cmc) which was 10.0, 40.0, 1.6, and 16.0 mmol dm-3, respectively. At their cmc's the interfacial area per molecule was 41 and 44 angstroms2 for NaPFN and HNaPFN and 63 and 66 angstroms2 for DCF4 and DHCF4 as determined from NR. From tensiometry the values obtained were 43, 51, 56, and 65 angstroms2, respectively. For all four compounds the surface excess measured by tensiometry, using a prefactor of 2 in the Gibbs equation, was in reasonable agreement with that obtained from NR. Partial structure factors of the adsorbed layers were determined for all four surfactants. The widths of the surfactant distributions were found to be significantly broadened by roughness at the interface. The widths of the solvent distribution were about 5 angstroms for the carboxylates and essentially 6 angstroms for the sulfosuccinates. In all cases the measured separations of the water and surfactant distributions were 5 angstroms, indicating a greater penetration of water into the sulfosuccinate layers. The contribution of capillary waves to the surface roughness was examined in order to assess the static disorder of molecules in the adsorption layer. The presence of the chain dipole does not appear to cause any significant structural differences normal to the interface.